2018
DOI: 10.3389/fpubh.2018.00118
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting and Eating: The Effect of Links and Likes on Food-Hypersensitive Consumers’ Perceptions of Tweets

Abstract: Moving on from literature that focuses on how consumers use social media and the benefits of organizations utilizing platforms for health and risk communication, this study explores how specific characteristics of tweets affect the way in which they are perceived. An online survey with 251 participants with self-reported food hypersensitivity (FH) took part in an online experiment to consider the impact of tweet characteristics on perceptions of source credibility, message credibility, persuasiveness, and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Social media posts often do not have the space to give as much detail as a website might to suggest expertise (e.g., references, evidence, associations with reputable organisations). Recent research has shown that links to other sources of evidence in social media posts can promote a sense of credibility [18], however the extent to which this can be considered the same as references or evidence cited within online sources needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media posts often do not have the space to give as much detail as a website might to suggest expertise (e.g., references, evidence, associations with reputable organisations). Recent research has shown that links to other sources of evidence in social media posts can promote a sense of credibility [18], however the extent to which this can be considered the same as references or evidence cited within online sources needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Seeking and sharing information are primary uses of the internet and social media [15][16][17][18]. In comparison to more traditional media, social media allows users to communicate in a reciprocal way, exchanging knowledge, sharing opinions or challenging information from others [19].…”
Section: Seeking Information From Experts On Social Mediamentioning
confidence: 99%
“…Individuals who are allergic to certain food items must avoid consuming allergens that could lead to a reaction called anaphylaxis (associated with breathing difficulties, sudden drop in blood pressure, and which may be fatal). Given these characteristics of food hypersensitivity, this is an ideal domain within which to explore attributions of expertise on social media because misinformation may have significant consequences [11,12]. The aim of this study was to explore how social media users and perceived experts in food hypersensitivities on social media construct meanings around expertise.…”
Section: Introductionmentioning
confidence: 99%
“…Seeking and sharing information are primary uses of the internet and social media [12,19-21]. In comparison with more traditional media, social media allow users to communicate in a reciprocal way, exchanging knowledge, sharing opinions, or challenging information from others [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the Internet is one of the main sources of food information (Jacob, Mathiasen, & Powell, ; Kuttschreuter et al, ; Ma, Almanza, Ghiselli, Vorvoreanu, & Sydnor, ; Redmond & Griffith, ; Tian & Robinson, ). Social media provide individuals with an easy‐to‐use tool to communicate with others which they use to find information and share their insights and concerns regarding new technologies (Barnett et al, ; Hamshaw, ; Kornelis, de Jonge, Frewer, & Dagevos, ; Kuttschreuter et al, ; Runge et al, ; Vidal, Ares, Machin, & Jaeger, ). This abundance of available viewpoints may be helpful as well as confusing (Regan et al, ).…”
Section: Introductionmentioning
confidence: 99%